1/

6x^4-(x^2-x)y^2-(y+12)x^2=-6

5x^4-(x^2-1)y^2-11x^2=-5

2/

( x-2011 )( 2011+2012\sqrt[3]{y-2013} )=1

( \sqrt[3]{x-2010}) ( y-4024 )= 2012

3/

Printable View

- November 18th 2011, 09:49 PMmathlinksSolve the following system of equations
1/

6x^4-(x^2-x)y^2-(y+12)x^2=-6

5x^4-(x^2-1)y^2-11x^2=-5

2/

( x-2011 )( 2011+2012\sqrt[3]{y-2013} )=1

( \sqrt[3]{x-2010}) ( y-4024 )= 2012

3/

- November 18th 2011, 10:21 PMProve ItRe: `\begin{cases}&6x^4-(x^2-x)y^2-(y+12)x^2=-6 \\ &5x^4-(x^2-1)y^2-11x^2=-5 \end{cas
- November 18th 2011, 10:49 PMmathlinksRe: `\begin{cases}&6x^4-(x^2-x)y^2-(y+12)x^2=-6 \\ &5x^4-(x^2-1)y^2-11x^2=-5 \end{cas